Fluid balance and thermoregulatory responses during wheelchair basketball games in hot vs. temperate conditions - Grossmann, F.; Perret, C.; Roelands, B.; Meeusen, R.; Flueck, J. L. (Nutrients, 2022)
The impaired vaso- and sudomotor functions limit sweat capacity in individuals with a spinal cord injury (SCI) and might increase the risk for heat-related illness and decreased performance, especially in hot conditions (HOT). This study investigated the differences in fluid balance and thermal responses between wheelchair basketball (WCB) games in HOT and temperate conditions (TMP). Eleven male WCB athletes (39.8 y, 82.8 kg) with SCI (lesion level C5-L4) participated, five in HOT (31 °C) and eight in TMP games (21 °C). Fluid balance, sweat rate, body core temperature, distance, velocity and thermal sensation were assessed. The relative change in body mass was higher in the HOT group (median: -0.35%, interquartile-range: 0.15%, p = 0.02) compared to TMP (+0.11%, 0.35%) group. The sweat rate was significantly higher in the HOT group (0.93 L/h, 0.58 L/h, p = 0.02) compared to the TMP groups (0.48 L/h, 0.19 L/h). Body core temperature increased significantly higher in the TMP group (1.05 °C, 0.15 °C, p = 0.01) compared to the HOT group (0.8 °C, 0.4 °C). The mean velocity (HOT: 1.12 m/s, 0.11 m/s, TMP: 1.07 m/s, 0.08 m/s, p = 0.54) did not differ between the games. The WCB game in HOT leads to significantly higher sweat rate and loss in body mass compared to TMP. Even relative body mass loss was less than 2%. Athletes thus have to be supported with enough fluid, especially during games in HOT.